Analisa Cakupan Area Signal Wireless Fidelity Terhadap Kualitas Layanan Dengan Metode Top Down Network - Raisul Azhar; I Putu Hariyadi; Heroe Santoso; I Gede Bagus Arthana (Prodi Ilmu Komputer Universitas Bumigora, 2022)
The proper placement of Access Point (AP) devices will affect network connectivity. This study applies the Top-Down Network Design Method which consists of the Needs Analysis Stage, Logic Design and Physical Design. This method is used to map processes that occur by identifying the needs of all internet users, designing network topology logic and determining the physical design of computer networks to be implemented. The purpose of this study is to determine the quality of connectivity from the proper Access Point range of Access Point devices and there are no deadzone s that occur and their impact on the quality of network service to users. The conclusion of this study is that it is able to improve the quality of connectivity from the reach of internet user Access Points so that there are no more dead zone coverage areas that occur in class 1 and 2 floor buildings as well as graduate buildings in the best coverage area in the 50m range for the 2.4GHz frequency. With a total of 450 users (students and lecturers), it is sufficient to provide a minimum of 125.25Mbps internet bandwidth and required 5 Access Point units and 3 wireless router units as a whole. Placement of different locations from AP devices determines good or bad quality of service produced and there is still a packet loss of 5.9% and a Throughput of 15.93Mbps in the lecturer room and in other areas.